2002
DOI: 10.1172/jci0215215
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of endothelial nitric oxide synthase accelerates atherosclerotic lesion formation in apoE-deficient mice

Abstract: Nitric oxide (NO) derived from endothelial NO synthase (eNOS) is regarded as a protective factor against atherosclerosis. Therefore, augmentation of eNOS expression or NO production by pharmacological intervention is postulated to inhibit atherosclerosis. We crossed eNOS-overexpressing (eNOS-Tg) mice with atherogenic apoE-deficient (apoE-KO) mice to determine whether eNOS overexpression in the endothelium could inhibit the development of atherosclerosis. After 8 weeks on a high-cholesterol diet, the atheroscle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
179
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 273 publications
(194 citation statements)
references
References 45 publications
13
179
2
Order By: Relevance
“…These factors play important physiological roles in vascular remodeling and wound repair and important pathological roles in vascular inflammation and in the development of atherosclerosis. In this respect it is interesting to note that despite the belief that NO is anti-atherosclerotic, recent studies showed that NOS3 promoted the development of atherosclerosis (40,41), as NOS3 knock-out mice are less prone to atherosclerosis, whereas overexpression of NOS3 in mice promotes atherosclerosis. Thus, the finding that NOS3 plays an important role in stimulating platelet secretion provides a potential mechanism for the role of NOS3 in promoting the development of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…These factors play important physiological roles in vascular remodeling and wound repair and important pathological roles in vascular inflammation and in the development of atherosclerosis. In this respect it is interesting to note that despite the belief that NO is anti-atherosclerotic, recent studies showed that NOS3 promoted the development of atherosclerosis (40,41), as NOS3 knock-out mice are less prone to atherosclerosis, whereas overexpression of NOS3 in mice promotes atherosclerosis. Thus, the finding that NOS3 plays an important role in stimulating platelet secretion provides a potential mechanism for the role of NOS3 in promoting the development of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, increase in endogenous eNOS inhibitor asymmetric dimethylarginine (ADMA), deficiency in co-factor tetrahydrobiopterin (BH 4 ), and deficiency in the substrate L-arginine have been proposed to cause so-called "uncoupling of eNOS" in atherosclerosis, a situation in which eNOS produces free radical superoxide anion instead of NO [17,19]. This mechanism may further contribute to inactivation of bioactive NO in atherosclerosis mediated by oxidative stress mediated by other enzymes such as NADPHoxidase [19].…”
Section: Controversy Of L-arginine Supplemental Therapy In Atherosclementioning
confidence: 99%
“…Most recently, a study with human coronary atherectomy specimens showed a higher eNOS gene expression in patients with acute coronary syndromes than those with stable angina [16]. It is of particular importance to note that Ozaki et al [17] recently showed acceleration of atherosclerotic lesion formation http://doc.rero.ch in ApoE -/-mice overexpressing bovine eNOS transgene. Controversial results were, however, reported by van Haperen et al [18] with the same experimental approach.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of transgenic mice that lack or overexpress NO synthases indicated that NO exerts both protective (4,5) and atherogenic (6)(7)(8)(9) effects. The double role of NO might explain why NO-generating drugs (e.g., glyceryl trinitrate) have not been reported to limit the progression of atherosclerosis in humans.…”
mentioning
confidence: 99%